EFFECT OF USING SILICA GEL AS ACTIVE PACKAGING TO THE LEMANG DETERIORATION IN LAHAT - Melati Pratama; Arief Marna Sonjaya (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2023)
The subject of this research was to analyze how the effect of silica gel concentration on Lemang water content, color, texture, taste and aroma. This study used a CRFD (Completely Randomized Factorial Design) by each two treatments and replications. The 1st treatment was silica concentrations (gram), it were 0, 1, 3 and 5. The 2nd treatment was time storage (days), it was 0, 3, 5 and 7. The data as a result were analyzed using ANOVA (analysis of variance) and SRD (the Smallest Real Difference) at a 95% confidence level. The application of silica gel on bamboo of Lemang gave a very significant effect to the Lemang water content, color and texture during 3 to 7 days storage. The best treatment from silica and time storage was 0 gram with 5 days storage. It had water content 55.67%, and the color was like by 3.8 points, the texture was little neutral by 2.16 points, the taste was little neutral by 2.30 points and the aroma was little dislike by 1.67 points.